2018
DOI: 10.1111/jcpt.12720
|View full text |Cite
|
Sign up to set email alerts
|

Low body mass index is a risk factor for hyperkalaemia associated with angiotensin converting enzyme inhibitors and angiotensin II receptor blockers treatments

Abstract: This study demonstrated that BMI provides useful information for the identification of potential risk for hyperkalaemia associated with ACEI and ARB treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…21 One explanation of the lower risk of HK in patients with obesity may be due to the increase in hyperaldosteronism among patients with high BMI, which leads to an increase in K + excretion. 22 In our study, a dialysate K + bath concentration ≥ 3 mEq/L was associated with lower odds of predialysis HK. Similarly, a previous DOPPS study found that after adjusting for confounding variables, there was an inverse relationship between dialysate K + bath concentrations and predialysis serum K + levels, with a change of À0.25 (95% CI, À0.26 to À0.24) mEq/L in serum K + per 1-mEq/L increase in dialysate K + bath concentration.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…21 One explanation of the lower risk of HK in patients with obesity may be due to the increase in hyperaldosteronism among patients with high BMI, which leads to an increase in K + excretion. 22 In our study, a dialysate K + bath concentration ≥ 3 mEq/L was associated with lower odds of predialysis HK. Similarly, a previous DOPPS study found that after adjusting for confounding variables, there was an inverse relationship between dialysate K + bath concentrations and predialysis serum K + levels, with a change of À0.25 (95% CI, À0.26 to À0.24) mEq/L in serum K + per 1-mEq/L increase in dialysate K + bath concentration.…”
Section: Discussionsupporting
confidence: 47%
“…This finding is consistent with a previous registry study of patients with CKD, which found that low BMI (<18.5 kg/m 2 ) was associated with increased odds of HK (OR, 1.60; 95% CI, 1.23–2.08) and high BMI (>30 kg/m 2 ) with lower odds of HK (OR, 0.77; 95% CI, 0.70–0.85) 21 . One explanation of the lower risk of HK in patients with obesity may be due to the increase in hyperaldosteronism among patients with high BMI, which leads to an increase in K + excretion 22 …”
Section: Discussionmentioning
confidence: 99%
“…BMI does not correlate with false or true hyperkalaemia, which is in contrast to a retrospective case-control Japanese study which concluded that patients on ACE-i or ARB with a lower BMI are more prone to hyperkalaemia with K>5.5 mmol/L. 10 Patients on ACE-i are more likely to have true hyperkalaemia compared with those on ARB. Patients on neither ACE-i or ARB are more likely to have false hyperkalaemia.…”
Section: Open Accesscontrasting
confidence: 92%
“…(1) Specimen collection time, (2) Time processed by central laboratory, (3) Polyclinic collected from, (4) Age, (5) Gender, (6) BMI based on most recent body weight and height, (7) Potassium levels,(8) presence of haemolysis (yes/no), (9) Repeat potassium (value and date) within 8 days of first K>5.5 mmol/L inclusive, (10) Polyclinic where repeat potassium was collected, (11) Creatinine at date of reported hyperkalaemia (µmol/L) and within 12 months prior, (12) Latest full blood count (FBC) results (within 6 months before and 6 months after first reported K>5.5 mmol/L) and (13) Medications prescribed within 6 months prior and 3 months after first hyperkalaemia (filtered). The filtered medications extracted were ACE-i (captopril, enalapril, lisinopril, perindopril, ramipril), ARB (candesartan, irbesartan, losartan, olmesartan, telmisartan, valsartan), potassiumsparing diuretics (spironolactone), potassium supplements (potassium chloride tablet, potassium citrate mixture) and the cation-exchange resin, SPS.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation